Antiamylolytic Activityof Okra (Abelmoschus esculentusL.) Pod Glycoprotein - Islam, Md. Shaharul; Karim, Md. Rezaul; Tan, Suat Hian; Rashid, Shah Samiur; Sarkar, Shaheen M. (2nd GNOBB Conference 2015, 2015)
The prevalence of diabetes is on a steady increase worldwide and it is now identified as one of the main threats to human health in the 21st century1. There has been an enormous interest in the screening of phytochemicals, specifically for the development of alternative medicines for type 2 diabetes, capable of delaying or preventingstarch hydrolysis and controllingblood glucose level. In Asian countries the okra podis consumed becauseit plays an important role in the human diet by supplying carbohydrates, proteins, vitamins, minerals and asan important source of antidiabetic compounds2. The goal of the present study was to provide in vitro evidence for potential inhibition of a-amylase and a-glucosidase activityby aqueous okra pod extract.